Identification of PSD-95 in the Postsynaptic Density Using MiniSOG and EM Tomography - Chen, Xiaobing; Winters, Christine; Crocker, Virginia; Lazarou, Michael; Sousa, Alioscka A.; Leapman, Richard D.; Reese, Thomas S. (Frontiers in Neuroanatomy, 2018)
Combining tomography with electron microscopy (EM) produces images at definition sufficient to visualize individual protein molecules or molecular complexes in intact neurons. When freeze-substituted hippocampal cultures in plastic sections are imaged by EM tomography, detailed structures emerging from 3D reconstructions reveal putative glutamate receptors and membrane-associated filaments containing scaffolding proteins such as postsynaptic density (PSD)-95 family proteins based on their size, shape, and known distributions. In limited instances, structures can be identified with enhanced immuno-Nanogold labeling after light fixation and subsequent freeze-substitution. Molecular identification of structure can be corroborated in their absence after acute protein knockdown or gene knockout. However, additional labeling methods linking EM level structure to molecules in tomograms are needed. A recent development for labeling structures for TEM employs expression of endogenous proteins carrying a green fluorescent tag, miniSOG, to photoconvert diaminobenzidine (DAB) into osmiophilic polymers. This approach requires initial mild chemical fixation but many of structural features in neurons can still be discerned in EM tomograms. The photoreaction product, which appears as electron-dense, fine precipitates decorating protein structures in neurons, may diffuse to fill cytoplasm of spines, thus obscuring specific localization of proteins tagged with miniSOG. Here we develop an approach to minimize molecular diffusion of the DAB photoreaction product in neurons, which allows miniSOG tagged molecule/complexes to be identified in tomograms. The examples reveal electron-dense clusters of reaction product labeling membrane-associated vertical filaments, corresponding to the site of miniSOG fused at the C-terminal end of PSD-95-miniSOG, allowing identification of PSD-95 vertical filaments at the PSD. This approach, which results in considerable improvement in the precision of labeling PSD-95 in tomograms without complications due to the presence of antibody complexes in immunogold labeling, may be applicable for identifying other synaptic proteins in intact neurons.